(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Incisional hernia (IH) after abdominal surgery is a well-known complication and its incidence continues to be 10-15% after laparotomy. The repair of IH has always been a challenge to the surgeon. Various operative techniques for the repair of IH are in practice; however, the management is not standardized. The sublay technique has been reported to be quite effective, with low recurrence rates and minimal complications. Objective: To assess the advantage and complications of sublay mesh repair of IH in comparison to onlay mesh repair. Methods: Prospective study of 63 patients undergoing repair of IH from 1st January 2013 to 1st February 2015 done in General Surgical Unit of Al-Imamein Al-kadhmein Medical City. 42 cases of IH were managed by onlay mesh repair and 21 cases of IH were managed by sublay mesh repair. Results: Post-operative complications like seroma and wound infection were comparable in both groups. In sublay group seroma formation was one patient (4.76%). Wound infection was in one patient (4.76%). No septic mesh was removed in the series. In onlay group, seroma formation was in 9 patients (21.42%); most of seroma occur in large IH repair, wound infection was in 2 patients (4.76%) and one septic mesh was removed. In sublay recurrence rate was 0%, in onlay recurrence rate was in one patient (4.76%). Conclusion: Sublay mesh although it is more time consuming and technically more difficult, however, it carries low recurrence rate and few postoperative wound complication. Keywords: Sublay, onlay, Mesh Repair, Incisional Hernia Citation: Hasan YA, Al-Helfy SHA, Jabur RT. Is sublay mesh repair for incisional hernia better than conventional onlay mesh repair? Iraqi JMS. 2020; 18(2): 138-144. doi: 10.22578/IJMS.18.2.8.